(untitled) (Third Sector Social Economic Review, 2026)
This study aims to examine women’s cooperatives operating in the Eastern Black Sea Region from a gender perspective. Women play a critical role in regional development and women’s economic empowerment. Women actively work through women’s cooperatives. This role has the potential to empower them both economically and socially. However, gender roles and existing inequalities make the existence of women’s cooperatives problematic. Joining a women’s cooperative or establishing one themselves requires a shift. This support can hinder the sustainability of women’s cooperatives. Furthermore, women’s cooperatives are supported and encouraged at the policy and practice levels through institutional structures for sustainable development. In this structure, 18 individuals who are members of women’s cooperatives operating in the Eastern Black Sea Region, which operate with flexible working practices, were included in the study. Data obtained through qualitative research was analyzed within the framework of themes and categories. The findings demonstrate the retention of women’s cooperatives through the transfer of numerous public institutions and the paving of ways for these agreements to become partners in their regions. Members continue to view the cooperative as an alternative state system rather than a mere business enterprise, seeking ongoing external support for its sustainability. Furthermore, women’s cooperatives appear to have the potential to reproduce gender inequality rather than transform it, and to develop a structure that reinforces existing sexist structures.